Analisis Pengaruh Investor Attention terhadap Initial Return IPO - Puspita Handayani (Universitas Pamulang, 2022)
The research objective is analyzing the effect of investor attention on the initial return of the IPO. This research is a quantitative research, with secondary data. Data collection method with documentation derived from the prospectus and SVI obtained through Bloomberg, Indonesia Stock Exchange and Google Trends The population of this study is 268 companies that conduct IPO on the IDX in the 2016- 2021 period. The sampling technique was purposive sampling, in order to obtain 263 companies. The result of this research is that investors attention has no effect on the initial return of the IPO.